2008
DOI: 10.1292/jvms.70.139
|View full text |Cite
|
Sign up to set email alerts
|

Functional Disorder of the Retina in Manganese-Deficient Japanese Quail Revealed by Electroretinography using a Contact Lens Electrode with Built-In Light Source

Abstract: ABSTRACT. Manganese deficiency results in neurological and skeletal defects, together with ultrastructural disarrangement of the retina in rats. Wild birds show a range of Mn concentrations in their tissues, including the liver, raising the possibility of Mn-related disorders in the wild. Electroretinography (ERG) provides a useful noninvasive approach to evaluate visual function. This method is especially useful in birds, as objective analysis of them is very difficult, while they have well-developed vision. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, high Mn exposure is also associated with potent neurotoxicity effects. Some studies found that animals fed with Mn-deficient diet for long periods can result in changes both on the morphology and function of the retina or optic nerve [16,17]. Contrast sensitivity was reported to be significantly reduced in heavy smokers compared to non-smokers, and mean serum Mn levels were significantly lower in smokers than in non-smokers [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, high Mn exposure is also associated with potent neurotoxicity effects. Some studies found that animals fed with Mn-deficient diet for long periods can result in changes both on the morphology and function of the retina or optic nerve [16,17]. Contrast sensitivity was reported to be significantly reduced in heavy smokers compared to non-smokers, and mean serum Mn levels were significantly lower in smokers than in non-smokers [18].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Trace elements deficiency, undernourishment, and exposure to drugs of abuse or alcohol induced ultrastructural changes in the ON, cornea, and retina. 25,26,29,[31][32][33][34][35][42][43][44][45][46][47][48][49][50][51][52][53] Figure 2 Mean density (a) and total number (b) of myelinated and unmyelinated fibres of the optic nerve in the control, anaemic, and recovered rats at postnatal day 32. Values are means ± SE for n ¼ 6; *Po0.05.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated a simple, easy to build and inexpensive experimental setup that includes contact lens electrodes with a built-in white light-emitting diode (LED) light source for ERG recording in rats. This type of electrode has been used in humans (Suzuki et al 1998, Tsuruoka et al 2004, dogs (Kim et al 2008, Yu et al 2007, Sasaki et al 2006, Maehara et al 2005, quail (Endo et al 2008) and rabbits (Maia et al 2004). There are four reports in the literature that describe its use in rats, but with a different ERG setup (Goto et al 2002, Grozdanic et al 2003, Yoneda et al 2003, Yamashita et al 2009.…”
Section: Introductionmentioning
confidence: 99%